REPRESENTASI BUDAYA POPULER PADA FENOMENA “CITAYAM FASHION WEEK” DI INDONESIA - Andriani, Viena Wanidha; Putri, Ellyana Ilsan Eka (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
Citayam Fashion Week as the form of street culture becomes a viral event not only in Indonesia but also in the other countries. The concept of popular culture presented in the event was very interesting to analyze. This research is a cultural studies with qualitative approach. The data is taken by internet access in the social media google and instagram. By Hall’s representation theory, this research wants to find how the popular culture is represented in the Citayam Fashion Week. The results of this study show that “fashion week”, “street style”, and “harajuku style” as the form of popular culture becomes the concepts that is represented in this event. It becomes the space of youth related to the freedom of expression and creativity of their fashion style.